دراسة الاستقرار النسبي لمماكبات الجزيئات 3-C3H3CXO، إذ إن X = H, F, Cl, Br, CH3، باستخدام طرائق الـ Ab initio المختلفة - بدوي محمد (Latakia University Journal -Basic Sciences Series, 2018)
درس الاستقرار النسبي لمماكبات الجزيئات 3-C3H3CXO؛ إذ إن X = H, F, Cl, Br, CH3، باستخدام الطرائق النظرية Ab.initio المختلفة، والتوابع الذرية الأساسية المختلفة، وحددت منحنيات الطاقة الكامنة (PES) للدوران الداخلي حول الرابطة المركزية للمجموعات CXO بالنسبة إلى حلقة البروبن، وكذلك دوران مجموعة المتيل في حالة الجزيء 3-C3H3C(O)CH3. وجد أن للجزيئات السابقة مماكبين مستقرين cis و trans، ويختلف الاستقرار النسبي لهذين الشكلين الفراغيين باختلاف X. قورنت نتائج هذا العمل مع تلك القيم النظرية والتجريبية للجزئيات c-C3H5CXO، إذ إن X=H,F,Cl,Br,CH3، وأجريت بعض الحسابات النظرية المتعلقة بفرق الطاقة والحواجر الكمونية لبعض مماكبات هذه الجزيئات في هذا العمل بهدف المقارنة. وجد أنه في حالة X=CH3، يحتفظ الجزيء 3-C3H3C(O)CH3 بمماكباتهcis و trans، خلافاً للجزيء c-C3H5C(O)CH3؛ إذ يتمتع بالمماكب cis، ومماكب آخر قريب من trans. The Study of The Relative Stabilization of Isomers of Molecules 3-C3H3CXO, where X=H, F, Cl, Br, CH3 was carried out using different ab initio Methods with different basis set. The potential energy surface (PES) of internal rotation of CXO groups relative to cyclopropene, and also of internal rotation of methyl group in molecule 3-C3H3C(O)CH3, was identified. It was found that the former molecules have two isomers, a trans and cis isomers. The relative stabilizations of these isomers are different as X change. The results of this work were compared with theoretical and experimental results of the molecules c-C3H5CXO, where X=H, F, Cl, Br, CH3. Some theoretical calculation related to energy differences and potential barriers of some isomers of these molecules were done in this work for the sake of comparison. It was found that where X=CH3, the molecule keep its isomers, cis and trans, contrary to molecule c-C3H5CXO, which has cis isomers and near trans isomers.